2017
DOI: 10.1016/j.tate.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceived professional space and their agency

Abstract: In order to increase student performance, governments stress the importance of standardization for teaching which is seen as a threat to teachers' professionalism. In this small-scale study we investigated the way teachers use their professional space in these changing circumstances. We studied eighteen cases of secondary education teachers indepth, using observations, interviews, and storylines. Our analyses revealed two types of trajectories which can be characterized by bounded and contested agency. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 26 publications
3
61
0
9
Order By: Relevance
“…Rammer forstås både som uttrykte krav og forventninger og som usagte normer i skolekulturen. Utgangspunktet for denne artikkelen er et internasjonalt prosjekt om laereres profesjonelle handlingsrom i tre land, Israel, Nederland og Norge (Oolbekkink-Marchand, Hadar, Smith, Helleve & Ulvik, 2017).…”
Section: Innledningunclassified
See 3 more Smart Citations
“…Rammer forstås både som uttrykte krav og forventninger og som usagte normer i skolekulturen. Utgangspunktet for denne artikkelen er et internasjonalt prosjekt om laereres profesjonelle handlingsrom i tre land, Israel, Nederland og Norge (Oolbekkink-Marchand, Hadar, Smith, Helleve & Ulvik, 2017).…”
Section: Innledningunclassified
“…Så langt finnes det lite empiri på laereres egen opplevelse av handlingsrom (Oolbekkink-Marchand et al, 2017). Svaret på hvordan de erfarer handlingsrommet, kan gi oss innsikt i hvordan de er i stand til å ta kontroll over sin egen praksis og til å styre ut fra egne mål.…”
Section: Innledningunclassified
See 2 more Smart Citations
“…To better understand Ms. Q's perception of her professional space and her agency, we drew on the insights gleaned from Oolbekkink-Marchand, Hadar, Smith, Helleve, and Ulvik (2017), who investigated 18 secondary school teachers' perceptions of how they exploited their teaching space and what drawbacks they experienced as a result of the exploitation of their space. Oolbekkink-Marchand et al (2017) reported that it was their teacher participants' experience with classroom teaching practice, school contexts as well as their relations with the school management and personal pedagogical values and beliefs that helped them exploit the professional space they inhabited.…”
Section: Teacher Agency From a Job-crafting Perspectivementioning
confidence: 99%